Medicinal plants of Sabah (North Borneo): Lest we forget - Carynn Tanbuda; Mazdida Sulaiman; Yong, Pauline Pau Lin; Nor Azizun Rusdi; Jaya Sathiya Seelan; Ng, Shean Yeaw; Fiffy Hasnidah Saikim; Mogana Rajagopal; Pang, Tze Ping Nicholas; Melanie Martos Garcia; Jhonnel Villegas; Shari Jeffrih; et al. (Taylor & Francis Group, 2025)
Context: The discovery of plants and bioactive compounds with the potential to become botanical or pharmaceutical drugs remains a cornerstone of drug innovation. Many of these valuable molecules originate from traditional botanical pharmacopeias, repositories of centuries-old knowledge that are often underappreciated in modern research. Objective: This review highlights the medicinal plants identified in Sabah from 1922 to 2024, analyzing their taxonomical distribution, uses, utilization among ethnic groups, and their potential for clinical uses. Methods: The data for this review were gathered from Google Scholar, PubMed, ScienceDirect, Web of Science, PubMed, the Internet Archive, and Google Books. A keyword combination of “Medicinal” and “Plants” and “Sabah” yielded 21,700 results. Each result was examined, and articles that did not contain information relevant to the topic or came from non-peer-reviewed journals were excluded. Each of the remaining 87 selected articles was critically reviewed to extract pertinent information. Results: A review of the available data indicates that 696 plant species are used in Sabah, including 412 angiosperms. These plants are primarily utilized to treat diseases or symptoms related to infections, digestive issues, injuries, and pains. Notably, 156 species employed by local Sabahan Dusunic, Murutic, and Kelabit ethnic groups remain unstudied in terms of their phytochemical and pharmacological properties, highlighting their potential for further investigation. Conclusion: Sabah’s medicinal plants offer tremendous potential for discovering natural products of therapeutic value.